Mechanisms of Neuronal Protection against Excitotoxicity, Endoplasmic Reticulum Stress, and Mitochondrial Dysfunction in Stroke and Neurodegenerative Diseases - Prentice, Howard (Oxid Med Cell Longev, 2015)
In stroke and neurodegenerative disease, neuronal excitotoxicity, caused by increased extracellular glutamate levels, is known to result in calcium overload and mitochondrial dysfunction. Mitochondrial deficits may involve a deficiency in energy supply as well as generation of high levels of oxidants which are key contributors to neuronal cell death through necrotic and apoptotic mechanisms. Excessive glutamate receptor stimulation also results in increased nitric oxide generation which can be detrimental to cells as nitric oxide interacts with superoxide to form the toxic molecule peroxynitrite. High level oxidant production elicits neuronal apoptosis through the actions of proapoptotic Bcl-2 family members resulting in mitochondrial permeability transition pore opening. In addition to apoptotic responses to severe stress, accumulation of misfolded proteins and high levels of oxidants can elicit endoplasmic reticulum (ER) stress pathways which may also contribute to induction of apoptosis. Two categories of therapeutics are discussed that impact major pro-death events that include induction of oxidants, calcium overload, and ER stress. The first category of therapeutic agent includes the amino acid taurine which prevents calcium overload and is also capable of preventing ER stress by inhibiting specific ER stress pathways. The second category involves N-methyl-D-aspartate receptor (NMDA receptor) partial antagonists illustrated by S-Methyl-N, N-diethyldithiocarbamate sulfoxide (DETC-MeSO), and memantine. DETC-MeSO is protective through preventing excitotoxicity and calcium overload and by blocking specific ER stress pathways. Another NMDA receptor partial antagonist is memantine which prevents excessive glutamate excitation but also remarkably allows maintenance of physiological neurotransmission. Targeting of these major sites of neuronal damage using pharmacological agents is discussed in terms of potential therapeutic approaches for neurological disorders.